MENJADI BIJAK MELALUI SEJARAH - Farid Abdullah (Universitas Trisakti, 2014)
AbstractThis is article about a book of Art history. The book aims have been exploratory rather than critical. The authors, Hugh Honour and John Fleming (1984), referred exposition to interpretation and evaluation, so far as they are separable. The appeal of some works of art in this book is never purely visual, it isjust simply to delight our eyes. It is heavy burden to bear in mind that these conceptions are peculiar to the West perspective. It try to vast a large horizon in both time and space, attention on historically prominent periods and areas,which are also those of most basic interest. Chapters are arranged chronogically, across a wide geographical panorama in order to allow crucial events in world history of humankind. This article also focus to history of photography, that was closely allied with both painting and print making, since of its invention in the 1830s. At last, history of art inevitably reflect the feelings and minds of their authors, who have been almost as diverse as the artists about whom they write, as diverse and many-sided as the works of art themselves.AbstrakTulisan ini adalah bedah buku tentang sejarah seni. Tujuan buku adalah melakukan penjelajahan daripada bacaan kritis. Penyusunnya, Hugh Honour dan John Fleming, memilih penjelasan terperinci dan sarat penilaian, yang sesungguhnya keduanya dapat terpisah. Karya-karya seni yang ditampilkan pada buku penuh visual, bermaksud untuk menyenangkan amatan pembaca. Beban besar dipikul buku ini, terkaitsudut pandang Barat yang rumit. Cakrawala luas ruang dan waktu dibentangkan luas pada buku ini. Penyusunan bab dibuat secara kronologis, merentang panorama geografis teramat lebar dalam rangka menjelaskan peristiwa-peristiwa penting sejarah umat manusia. Tulisan ini juga memusatkan diri pada sejarah fotografi, yang memiliki hubungan erat dengan seni lukis dan cetak mencetak, sejak temuan pada tahun 1830. Pada akhirnya, sejarah adalah cermin dari perasaan dan pikiran penulisnya, yang selalu berbeda-beda seperti halnya seniman yang mereka tulis. Berbeda-beda dan memiliki berbagai sudut pandang seperti halnya karya seni.*) Staf Pengajar Fakultas Pendidikan Seni dan Desain, Universitas Pendidikan